Women’s perspective on gender based violence as an impoverishment factor - Castañeda Eugenio, Nancy (2015)
Objectives: To determine women’s perspective on gender based violence as a factor of families’ impoverishment in Huanuco province. Design: Nonexperimental, descriptive, correlational, explanation  study. Setting: Office of the Family, Women’s Emergency Center, Commissioner of Police, and NGO Peace and Hope. Participants: Women victims of family violence. Interventions: Between August and December 2008 we applied an interview guide, a questionnaire and a data collection sheet to a sample of 200 women victims of family violence. Methods used were inductive-deductive analysis and synthesis. Main outcome measures: Physical abuse. Results: Physical abuse was present in 78% of cases; 39% of women were devoted to household duties (housewives) that reflected they were economically dependent. Prevailing machismo and authoritarianism in our society conditioned acts of violence (51%) as well as the economic problems facing the family (27%). Women victims of violence felt that poverty is not having money to cover food, education and housing basic needs (89%). The perception of women victims of violence to stop being poor was that they should have to start working (29%). They also admitted that due to abuse they are unable to work (17%) and suffered constantly from various diseases (9%). Conclusions: Violence is a factor of impoverishment that leads to human capital deterioration as women decrease their ability to enter the labor market, have destroyed their self-esteem and feel unable to cope with abuse.